Absent state, linguistic segregation of Quechua and its social implications in the Mantaro Valley - Salazar Solano, Roberto (2022)
In this so far unpublished interview, carried out on September 20, 2019 in the city of Huancayo, doctor Rodolfo Cerrón-Palomino (Ph D. in Linguistics, University of Illinois at Urbana-Champaign), with honorary doctorate from the National University of the Center of Peru, exposes his reflections on the social problems of the Quechua language and the constant segregation of its speakers. He provides us an account and reason, from an interdisciplinary approach, of the colonial history whose effects radiates up to the present, evidencing, in an absent State, official educational strategies and private ones that, buried and at the same time manifested, turn out to be symbolically violent, stigmatizing the practice and knowledge of the comunolects in the Mantaro valley. Professor Cerrón-Palomino also explains in detail his work in interpreting and modernizing the vocabulary compiled by the Franciscan huancaíno, José Francisco María Ráez, in the first decades of the XXth century, by editing philologically the Diccionario huanca quechua-castellano/ castellano-quechua of the illustrius Franciscan friar. Finally, reference is made to his tenacious investigation on the Puquina language, which the interviewed proposes as the ancestral tongue of the Incas.